Ectoparasites of Wild Rats (Rattus spp.) in Banyuwangi: Prevalance, Diversity, and Potential Risks - Tanjung, Aldi Gusnizar Rizaldy; Wardhana, April Hari; Yudhana, Aditya; Maulana, Muhammad Rizal; Kurnianto, Muhammad Aqil; Santosa, Gusti Ayu Illiyin Putri; Khairunnisa, Hanifa Khansa; Putri, Valerie Brilianda; Koesdarto , Setiawan (Universitas Airlangga, 2025)
This study aimed to determine the prevalence of ectoparasite infestation and all types of ectoparasites that infest wild rats (Rattus spp.) from three villages in Banyuwangi Subdistrict, namely Lateng Village, Kampung Mandar Village, and Kepatihan Village. A total of 100 wild rats of the species Rattus norvegicus and Rattus tanezumi were collected from Lateng Village, Kampung Mandar Village, and Kepatihan Village. Samples were anaesthetised based on the standard operational procedure of ethical testing and combed to obtain ectoparasites that predilect on the surface of the rat body. Ectoparasites were identified using the whole mount method natively with 10% KOH fixation, dehydration, and clearing to see the morphology of the ectoparasites.The results showed that the prevalence of ectoparasite infestation was 94% from three villages in Banyuwangi Subdistrict, consisting of 94 fleas, 38 lice, and 1,392 mites. The results of ectoparasite identification obtained five genus namely Xenopsylla, Polyplax, Hoplopleura, Laelaps, Ornithonyssus. Further research is needed to determine the prevalence of infestation and diversity in wild rats (Rattus spp.) in Indonesia.